SEXUAL SADISM DISORDER AS A FORM OF PSYCHOPATHIC PERSONALITY ON THE MAIN CHARACTER IN THE NOVEL FIFTY SHADES DARKER BY E.L. JAMES - Monica Argitha Sakthiyani; Shita Dewi Ratih; Ni Made Widisanti S (Universitas Pakuan, 2019)
Abstract This research discusses sexual sadism disorder as the form of the main character’s psychopathicpersonality in the novelFifty Shades Darker by E.L. James. The purpose of this research is to denote the characteristics of psychopath and to analyze the process and the cause that lead the main character to behave psychopathically. The research is conducted by means of descriptive analysis method. The result of this research shows that the main character has a psychopathic personality disorder in the form of sexual sadism disorder based on behaviors that denotes psychopathic characteristics, such as charm, egocentric, lack of remorse, lack of empathy, deceitful and manipulative, shallow emotions, impulsive, poor behavior controls, need for excitement, lack of responsibility, early behavior problems, adult antisocial behavior. The psychological trauma in his childhood and the experience of sexual intercourse with Elena in the past of the main character is the process and the cause in the formation of the main character’s sexual sadism disorder. Keyword: fifty shades darker, psychopathy, sexual sadism